Religious Tolerance in the View of Hadith for Peace of Worship in Indonesia: A Study of Takhrij and Syarah - Alif Fadhilah; Dadang Darmawan; Wahyudin Darmalaksana (Tunas Harapan Ummat Foundation, 2025)
This study aims to discuss the hadith about religious tolerance. This study uses a qualitative approach by applying the descriptive- analytical method. The formal object of this research is the science of hadith, while the material object is the hadith about religious tolerance in the history of Bukhari no. 38. The results and discussion of this study indicate that the status of the hadith is of authentic quality that meets the qualifications of maqbul ma'mul bih for the practice of Islam. This study concludes that the hadith narrated by Bukhari no. 38 relevant to be used as motivation to develop religious tolerance in Indonesia.